Effects of zinc oxide nanoparticles on early-age hydration and the mechanical properties of cement paste. (30th August 2019) - Liu, Jintao; Jin, Hang; Gu, Chunping; Yang, Yang
Highlights: Nano-ZnO particles prolonged the setting times of cement paste. Nano-ZnO affected the hydration reaction of cement at the early age. The induction period of cement hydration was extended by nano-ZnO. Nano-ZnO improved long-age strength of cement paste. Abstract: Zinc oxide nanoparticles (nano-ZnO) were dispersed uniformly into cement paste by using ultrasonic treatment, and the effects of nano-ZnO on the setting time, strengths, hydration, and microstructure of the cement paste were investigated. The addition of nano-ZnO to cement paste showed a remarkable influence on the early hydration process of the cement paste, whose setting time increased drastically when the content of nano-ZnO was only 0.2 wt% (by weight of cement). The isothermal calorimetry and electrical resistance tests showed that the addition of nanoparticles can prolong the induction period of cement hydration and influence the hydration rate during the acceleration period. The mechanical test results indicated that long-age strengths of cement paste were improved with the increase of nano-ZnO concentrations. Furthermore, nano-ZnO refined the pore diameter distribution and formed a compact microstructure of the cement paste at 28 days.